Peran Tutor Sebaya dalam Meningkatkan Kemampuan Vokal Mahasiswa pada Mata Kuliah Mayor Vokal di Program Studi Pendidikan Musik Universitas Lampung - Rintia Marsyanda; Riyan Hidayatullah; Ahmad Sugandi (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Objective: This study aims to analyze the role of peer tutors in improving students' vocal abilities in the vocal major course at the Music Education Study Program, University of Lampung, with a focus on learning motivation, vocal technique mastery, and musical interpretation skills. Method: The study employed a descriptive qualitative approach with a case study design through in-depth interviews, direct observation of practice sessions, and repertoire documentation. Data analysis was conducted using the Miles & Huberman interactive model encompassing data reduction, data presentation, and conclusion drawing. Results and Discussion: Peer tutors significantly contribute to improving students' vocal abilities through direct technical guidance, constructive feedback, and sustained motivational support. Peer tutoring interactions encourage students to practice consistently, build training discipline, and strengthen mastery of vocal techniques and musical interpretation. The collaborative learning environment fostered by peer tutors also enhances students' intrinsic motivation, self-confidence, and performance readiness. Conclusion: Peer tutors serve as a key factor in supporting the development of students' vocal abilities effectively and sustainably through technical guidance, motivation, and direct feedback that build self-confidence and practice consistency.